Comparison between RANS and 3D-PTV measurements of Newtonian and non-Newtonian fluid flows in a stirred vessel in the transitional regime. (5th March 2023) - Romano, M.G.; Alberini, F.; Liu, L.; J. H. Simmons, M.; Stitt, E.H.
Highlights: 3D-PTV measurements and RANS of transitional flows in a lab-scale stirred vessel have been cross-validated. The turbulence model had little effects on the main flow. The discretisation scheme had significant effects on the turbulent quantities. Non-Newtonian rheology exacerbated the difficulties associated to RANS of transitional flows. Abstract: Newtonian and non-Newtonian fluid flows in a vessel ( T = H = 180 mm) stirred with a Rushton turbine ( C = D = T / 3 ) have been simulated in CFD using steady RANS in the transitional regime ( 183 ≤ R e ≤ 1, 086 ). The numerical results have been compared against 3D-PTV measurements. For Newtonian fluids, the different turbulence models predicted the same mean flow, which matched well the experimental velocity data. The standard k - ε model predicted the power numbers closest to expected values and resolved 80 % (at R e = 943 ) and 89 % ( R e = 86 ) of the total energy dissipation. Simulations of the non-Newtonian flows presented challenges. For shear thinning rheology, the simulated mean flow patterns did not correspond to the measured ones. CFD also predicted a higher mean velocity, compared to PTV. For yield stress fluids, the numerical predictions of the cavern boundaries were in reasonably good agreement with the experimental observations.